Management of Necrotizing Pneumonia and Pulmonary Gangrene: A Case Series and Review of the Literature - Neela Chatha; Dalilah Fortin; Karen J Bosma (Canadian Respiratory Journal)
BACKGROUND: Necrotizing pneumonia is an uncommon but severe complication of bacterial pneumonia, associated with high morbidity and mortality. The availability of current data regarding the management of necrotizing pneumonia is limited to case reports and small retrospective observational cohort studies. Consequently, appropriate management for these patients remains unclear.